Investigating the safety and activity of the use of BTT1023 (Timolumab), in the treatment of patients with primary sclerosing cholangitis (BUTEO): A single-arm, two-stage, open-label, multi-centre, phase II clinical trial protocol. Issue 6 (3rd July 2017) - Arndtz, Katherine; Corrigan, Margaret; Rowe, Anna; Kirkham, Amanda; Barton, Darren; Fox, Richard P; Llewellyn, Laura; Athwal, Amrita; Wilkhu, Manpreet; Chen, Yung-Yi; Weston, Chris; Desai, Amisha; et al.
Abstract : Introduction: Primary sclerosing cholangitis (PSC) is a progressive inflammatory liver disease characterised by relentless liver fibrosis and a high unmet need for new therapies. Preventing fibrosis represents an important area of interest in the development of vital new drugs. Vascular adhesion protein-1 (VAP-1) drives inflammation in liver disease, and provision of an antibody against VAP-1 blunts fibrosis in murine models of liver injury. Methods and analysis: BUTEO is a single-arm, two-stage, open-label, multi-centre, phase II clinical trial. Up to 59 patients will receive treatment with anti-VAP monoclonal antibody, BTT1023, over a 78-day treatment period. Adults with PSC and a serum alkaline phosphatase (ALP) of at least 1.5 times the upper limit of normal will be included. Our primary outcome measure is a reduction in ALP by >25% from baseline to Day 99. Secondary outcome measures include safety and tolerability, changes pre therapy/post therapy in circulating serum VAP-1 as well as imaging findings. The first patient participant was recruited on 08 September 2015. Ethics and dissemination: This protocol has been approved by the Research Ethics Committee (REC, reference 14/EM/1272). The first REC approval date was 06 January 2015 with three subsequent approved amendments. This article refers to protocol V3.0, dated 16 March 2016. Results will be disseminated via peer-reviewed publication and presentation at international conferences. Trial registration: The trial is registered with the European Medicines agency (EudraCT: 2014-002393-37), the National Institute for Health Research (Portfolio ID: 18051) and ISRCTN: 11233255. The clinicaltrials.gov identifier is NCT02239211 . Pre-results.